2023
DOI: 10.3389/feduc.2023.1124983
|View full text |Cite
|
Sign up to set email alerts
|

Flourish-HE: An online positive education programme to promote university student wellbeing

Abstract: Student mental health and wellbeing is both a priority and area of challenge within Higher Education, with providers seeing an increased demand for mental health, counselling and wellbeing support. The current paper argues that an effective preventative approach to supporting university student wellbeing is one that: (a) addresses student wellbeing using a holistic approach; (b) is underpinned by a comprehensive wellbeing theory; (c) aims to promote key dimensions of individual and collective wellbeing; and (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 139 publications
1
5
2
Order By: Relevance
“…Previous studies have reported that stress awareness courses ( Peterson et al, 2023 ), the Flourish-HE program ( Morgan et al, 2023 ), flower essence bouquets ( Albuquerque and Turrini, 2022 ), and visualization meditation ( Aksu and Ayar, 2023 ) can increase students’ SWB. The results of the present study are in line with previous study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported that stress awareness courses ( Peterson et al, 2023 ), the Flourish-HE program ( Morgan et al, 2023 ), flower essence bouquets ( Albuquerque and Turrini, 2022 ), and visualization meditation ( Aksu and Ayar, 2023 ) can increase students’ SWB. The results of the present study are in line with previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have reported the significant effects of PPI programs on improving students’ well-being in different contexts, such as a program based on the PERMA model (Flourish-HE) in a British context ( Morgan et al, 2023 ), a PPI in an intensive English program in an American context ( Rogers et al, 2023 ), a school-based happiness mentoring program in a Singapore context ( Metrat-Depardon and Teo, 2023 ), and a gratitude-based exercise and a strengths-based exercise in a Malaysian context ( Senf and Liau, 2013 ). The present study is in line with earlier studies, which show that a PERMA model-based PPI program can improve students’ SWB in the Chinese context.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations